COVID-19 and the cutting of college athletic teams. Issue 11 (18th August 2020) - Swanson, Ryan; Smith, Allison B.
Abstract: Almost as soon as the NCAA announced the cancelation its 2020 "March Madness" basketball tournament, college administrators began moving to cut sports from their schools' portfolios. This study explores the effects of the COVID-19 pandemic on college athletics. It examines the historical and sociological context surrounding the decisions to eliminate athletic programs (affecting nearly 2, 500 athletes at the time of writing) at universities across the country. Drawing on research surrounding the implementation of Title IX, the authors examine how college athletics' most recent crisis caused university leaders to once again cut sports in the name of gender equity.